PERENCANAAN DMA BERBASIS IOT UNTUK MENURUNKAN KEHILANGAN AIR DI KOTA AMBON - Masduqi, Ali; Nanda, Fahreza Alvian; Adhi, Bagas Wahyu (Universitas PGRI Semarang, 2023)
Access to clean water is the right of every citizen that the government must fulfill, both the central government and local governments, through drinking water business entities, namely PDAM. The performance of a PDAM represents the quality level of drinking water administration in an area. Only now, the high loss of drinking water has become problematic for PDAMs in improving their performance. One of the PDAMs with a high loss of drinking water is PDAM Tirta Yapono, Ambon City, with a water loss rate of 69.85%. In this paper, an effort is made to reduce water loss in PDAM Tirta Yapono by establishing a DMA in the Wainitu Village based on the existing condition of the pipeline, along with the number of sensors and instrumentation needed. SCADA and asset management implementation are also designed to support DMA's performance in reducing water loss. SCADA's role in reducing water loss facilitates the implementation of step tests and automation of monitoring activities for the distribution process and water quality by placing several instruments in the distribution network. Monitoring with SCADA will provide accurate data. Then, asset management also plays a role in reducing water losses because the information contained in asset management is used as material for preparing a strategy to reduce water losses following the priorities and capabilities of PDAM Tirta Yapono.